Reversible piezochromism in a molecular wine-rack1. Issue 53 (7th July 2015) - Harty, Elena L.; Ha, Alex R.; Warren, Mark R.; Thompson, Amber L.; Allan, David R.; Goodwin, Andrew L.; Funnell, Nicholas P.
<x xml:space="preserve">Abstract</x> Coupling of a 'wine-rack' lattice motif with molecular flexibility leads to a large piezochromic response in an organic material.